Proceedings of the 2017 Federated Conference on Computer Science and Information Systems 2017
DOI: 10.15439/2017f376
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Fire Safety Education System on Campus based on Virtual Reality Technology

Abstract: Abstract-Fire safety education is essential to every student on campus. Fire safety knowledge learning and operational practice are both important. There is evidence that the virtual reality (VR) based educational method can be a novel and effective approach to learning and practice. However, the existing VR-based system for fire safety education has some shortcomings such as lack of interactivity and high equipment complexity, resulting in low practicability. In order to improve the effect of fire safety educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 9 publications
(9 reference statements)
1
17
0
1
Order By: Relevance
“…On the other hand, the systematic review by Radianti, Majchrzak, Fromm, and Wohlgenannt (2020) on the use of IVR in higher education showed that most of the reviewed studies do not specify a method for measuring learning outcome in their evaluation. Studies which have evaluated the learning effectiveness have used both subjective criteria, such as self‐assessments using questionnaires and objective criteria, such as the time required to complete a task in reality after the virtual training, the number of errors, knowledge tests or judgements by experts (Bucher et al ., 2019; Bun, Trojanowska, Ivanov, & Pavlenko, 2018; Kamińska et al ., 2017; Zhang, Suo, Chen, Liu, & Gao, 2017). Measuring the effectiveness of VR through learning transfer can be challenging, since, as the above‐mentioned discourse in transfer research shows, there are not only different views on the occurrence of a transfer, but also on its measurement (Barnett & Ceci, 2002; Bossard et al ., 2008; Reed, 2012; Singley & Anderson, 1989).…”
Section: Theoretical Background and State Of Researchmentioning
confidence: 99%
“…On the other hand, the systematic review by Radianti, Majchrzak, Fromm, and Wohlgenannt (2020) on the use of IVR in higher education showed that most of the reviewed studies do not specify a method for measuring learning outcome in their evaluation. Studies which have evaluated the learning effectiveness have used both subjective criteria, such as self‐assessments using questionnaires and objective criteria, such as the time required to complete a task in reality after the virtual training, the number of errors, knowledge tests or judgements by experts (Bucher et al ., 2019; Bun, Trojanowska, Ivanov, & Pavlenko, 2018; Kamińska et al ., 2017; Zhang, Suo, Chen, Liu, & Gao, 2017). Measuring the effectiveness of VR through learning transfer can be challenging, since, as the above‐mentioned discourse in transfer research shows, there are not only different views on the occurrence of a transfer, but also on its measurement (Barnett & Ceci, 2002; Bossard et al ., 2008; Reed, 2012; Singley & Anderson, 1989).…”
Section: Theoretical Background and State Of Researchmentioning
confidence: 99%
“…The ability of EduAPPLE and, thus, GBL, to increase the user's skills, seems contrary to the disposition of firefighter instructors toward the use of game‐based training tools. By considering that such a system was already developed in cooperation with the Swedish Rescue Services Agency [3,4], and that similar systems are still being developed , it leads to the conclusion that their rejection of GBL was unjustified, although the Swedish training system SIDH [3,4] was not intended to replace the conventional training, but merely to serve as a complement to the former. Additionally, SIDH already incorporates heat, along with physical and psychological stress factors, which was the main concern of the instructors while developing SIN.…”
Section: Resultsmentioning
confidence: 99%
“…Williams‐Bell et al give us some insight into those efforts, which continue to this day for example, Ref. . Although researchers continue to use virtual worlds even for the training of first responders, the commercial firefighting training software like ComandSim, RS Incident command, XVR, and FireStudio, limit themselves to training tactics and incident management rather than first responder action (e.g., how to enter the house on fire correctly, or how to search for and rescue the residents).…”
Section: Methodsmentioning
confidence: 99%
“…Concerning learning games and safety, in 2017 Zhang et al designed a framework for fire safety education implemented according to the combination of relevant fire safety education theory and immersive VR technology. Using an HTC VIVE helmet equipment for the user test, they again proved the effectiveness of this technology to help students learn fire safety knowledge, master fire safety skills and improve fire safety education effect [15]. Another example of immersive experience in safety education is the game developed by Vega et al in 2017.…”
Section: Serious Gamesmentioning
confidence: 95%